Composite material process monitoring using optical fibre grating sensors - Buggy, Stephen J. (Cranfield University, 2008)
In this thesis a long period grating (LPG) based sensor is investigated as a possible alternative to current process monitoring sensors used in the manufacture of composites to monitor cure. An LPG is demonstrated as a means of monitoring the cure of a UVcured epoxy resin. The wavelength shift of the attenuation bands were measured during the cure of the resin and compared with measurements made using a fibre optic Fresnel based refractometer. The results showed a good correlation (6 x 10 -3 rius) and illustrate the potential of the techniques for non-invasive composite material cure monitoring. Alternative fibre grating methods; a chirped LPG sensor, an in-fire Mach-Zehnder interferometer and a tilted fibre Bragg grating sensor, are also presented to demonstrate the versatility of grating based sensors for flow, high sensitivity refractive index and multi-parameter sensing, respectively. Demonstrations of LPG sensors in industrial applications are also presented and highlight the technical issues of integrating such devices in composite components and composite manufacturing processes.